HUBUNGAN PENERAPAN PROGRAM K3 DENGAN PERILAKU KERJA PADA PEKERJA PROYEK PEMBANGUNAN APARTEMEN PONDOK CABE, TANGERANG SELATAN TAHUN 2022 - Alifia Azzahrah Rahmayanti, (2022)
Human resources are irreplaceable resources. Human resources cannot be separated from occupational safety and health issues. Work behavior that has a negative impact on the number of work accidents. This study aims to determine whether there is a relationship between the implementation of the K3 program and work behavior in the construction project workers of the Pondok Cabe Apartment, South Tangerang in 2022. This study used a cross-sectional study design and sampling with accidental sampling technique of 92 workers. Analysis of the data used in the form of univariate and bivariate using the chi-square test. The results of the bivariate analysis showed that there was a relationship between tenure (POR=9.1; 95% CI=3.3-23.6), OSH policy (POR=7.8; 95% CI=2.9-20.7) . ), OSH communication and training (POR=25.6; 95% CI=8.1-81), accident inspection and investigation (POR=3.6; 95% CI=1.5-8.6) and supervision ( POR=4.3; 95% CI=1.7-10.7) with work behavior. It is expected that the company will further improve its implementation in implementing the existing K3 program, because with a good K3 program it will increase workers' self-awareness so that they behave safely so that the risk of work accidents will also decrease.